Domestic Resource Mobilisation for Sustainable Healthcare Financing in Nigeria: A Review - Amina Idris Bello; Maryam Abimbola Jimoh; Abdul-Rasheed Olalekan Tijani; Hafsat Abolore Ameen (Nigerian Postgraduate Medical Journal)
Domestic resource mobilisation (DRM) is vital for achieving sustainable healthcare financing in Nigeria, where dependence on external funding and oil revenues has long hindered health sector progress. The Nigerian healthcare system faces persistent challenges, including inadequate funding, inefficiencies and limited access to essential services, particularly in rural areas. This paper explores the challenges and prospects of DRM as a means of financing healthcare in Nigeria. A Medline search and a search of other internet search engines were carried out for published studies on healthcare financing in Nigeria, Africa and worldwide, we also examined policy documents and healthcare financing data to analyse the potential of DRM in Nigeria. A total of 38 publications were reviewed revealing that mechanisms such as general tax revenue, social insurance systems and community-based health insurance are central to DRM efforts. However, challenges such as inadequate budgetary allocations, corruption, poor database management and the emigration of health workers persist. Despite these obstacles, there are promising prospects, including increased tax revenue, development of the domestic capital market and the potential for sustainable and equitable healthcare financing through public–private partnerships. To harness these opportunities, the Nigerian government must implement effective policies, strengthen governance structures and promote transparency and accountability. DRM offers a promising path towards reducing dependency on external aid and achieving a more resilient and equitable healthcare system in Nigeria.